Odissi Vilas : Sacred dance of India (2005)
[Dt.:] Odissi Vilas ist eine NGO aus San Francisco (USA), die sich die Förderung und Vermittlung der tänzerischen Tradition Orissas zum Ziel gesetzt hat. Ihr Leiter ist Vishnu Tattva Das, selbst ein profilierter Tänzer. Auf der Homepage findet man ausführliche Informationen über die Geschichte und kulturelle Verankerung dieser Tanzformen. Außerdem gibt es hier einen Veranstaltungskalender. Diese Organisation gibt auch Kurse im Odissi- Tanz. - [Engl.:] Odissi Vilas is an NGO from San Francisco (USA) aiming to promote the dancing traditions of Orissa and to display these to a larger audience. It is headed by Guru Vishnu Tattva Das, himself a prolific dancer. This page features extensive information about the history and culture of Odissi dance. There is also a calendar of events here. This organisation also gives courses in Odissi dance